The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1128/cvi.00711-14
|View full text |Cite
|
Sign up to set email alerts
|

Open-Label Trial of Immunogenicity and Safety of a 13-Valent Pneumococcal Conjugate Vaccine in Adults ≥50 Years of Age in Mexico

Abstract: g This open-label multicenter clinical trial conducted in Mexico assessed the immunogenicity and safety of a 13-valent pneumococcal conjugate vaccine (PCV13) in adults >50 years of age not previously vaccinated with the 23-valent pneumococcal polysaccharide vaccine (PPSV23). The PCV13 elicited a robust immune response in this study population, as reflected by the magnitude of fold rises in functional antibody levels measured by serotype-specific opsonophagocytic activity (OPA) assays before and 1 month after v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…In addition to the phase III studies, an open-label study in PPSV23-naive adults C50 years of age (n = 324) in Mexico showed robust immune responses in terms of OPA GMTs for vaccine serotypes at 1 month following PCV13 administration [30]. For most serotypes, overall immune responses were higher than those previously reported in similar adult populations in the USA or Europe.…”
Section: Immunogenicitymentioning
confidence: 88%
See 1 more Smart Citation
“…In addition to the phase III studies, an open-label study in PPSV23-naive adults C50 years of age (n = 324) in Mexico showed robust immune responses in terms of OPA GMTs for vaccine serotypes at 1 month following PCV13 administration [30]. For most serotypes, overall immune responses were higher than those previously reported in similar adult populations in the USA or Europe.…”
Section: Immunogenicitymentioning
confidence: 88%
“…The modelling analysis of changes in outcomes attributable to PCV13 showed statistically significant (p \ 0.05) reductions of 37 % for IPD (95 % CI 20-51), 32 % (95 % CI 17-44) for noninvasive pneumococcal or lobar pneumonia and 12 % (95 % CI 6-17) for all-cause pneumonia among adults aged 18-39 years. There were also significant reductions in hospital admissions for noninvasive pneumococcal or lobar pneumonia in adults aged 40-64 years (by 25 %; 95 % CI [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and in older adults aged C65 years (by 34 %; 95 % CI 27-41), and for IPD in those aged C65 years (by 29 %; 95 % CI . These findings suggest a strong and rapid development of herd protection.…”
Section: Postmarketing Surveillance Studiesmentioning
confidence: 99%
“…AlPO 4 = aluminum phosphate; PCV13 = 13-valent pneumococcal conjugate vaccine; PPSV23 = 23-valent pneumococcal polysaccharide vaccine; TIV = trivalent inactivated influenza vaccine. A = South Africa 7 ; B = Japan 8 ; C = Japan 9 ; D = Mexico 10 ; E = Europe 11 ; F = United States and Sweden 13 ; G = United States and Europe 12 ; H = United States. 4-6 …”
Section: Resultsmentioning
confidence: 99%
“…No studies on the effectiveness of PNEU-C-13 vaccine were identified through the literature search. Efficacy data of PNEU-C-13 to prevent IPD and CAP in adults who were immunocompetent at enrollment were reported in one trial (5) and three trials provided data on vaccine immunogenicity in immunocompetent and immunocompromised adults (6)(7)(8).…”
Section: Resultsmentioning
confidence: 99%